Syringes and catheters – prospects for overcoming import dependence in the context of the implementation of the national project “Science” - T. N. Erivantseva (Ekonomika Nauki)
As part of the implementation of the approved presidential decrees “On the strategy of scientific and technological development of the Russian Federation” and the national project “Science”, the Russian Federation should take leading positions in a number of scientific areas, including taking by 2024 the 5th place in the amount of patent applications for inventions. The current patent activity of domestic developers in the field of devices for administering drugs to the body or applying them onto the skin of a person is analyzed. A comparison study of inventive activity of domestic and foreign developers is presented. The data obtained demonstrate the extremely low patent activity of domestic developers compared with their foreign colleagues.